2014
DOI: 10.1521/soco.2014.32.5.466
|View full text |Cite
|
Sign up to set email alerts
|

The Ugly Duckling Effect: Examining Fixed versus Malleable Beliefs about Beauty

Abstract: Storybook tales, movies, and beauty magazines often communicate the message that beauty is malleable. Malleable beliefs are generally found to be beneficial, but this is not the case in the beauty domain. Across two studies, we found that the "beauty is malleable" belief puts women (but not men) at risk for harmful appearance concerns, such as basing their selfworth on physical attractiveness, increased appearance anxiety, and increased interest in cosmetic surgery. These results were found when beauty beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Furthermore, according to the findings of Boursier and Manna (2018b), boys (compared to girls) appeared to indicate that excitement, sexual fantasies and feelings were important aspects of selfies. With regard to appearance concerns, according to previous studies (Burkley, Burkley, Stermer, Andrade, Bell, & Curtis, 2014;Cusumano & Thompson, 1997;Dakanalis et al, 2016;Jones et al, 2004;Zimmer-Gembeck, Webb, Farrell, & Waters, 2018), in the present study, girls reported higher levels of social appearance anxiety compared to boys. Finally, the present study did not find any statistically significant difference between girls' and boys' problematic social media use scores.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, according to the findings of Boursier and Manna (2018b), boys (compared to girls) appeared to indicate that excitement, sexual fantasies and feelings were important aspects of selfies. With regard to appearance concerns, according to previous studies (Burkley, Burkley, Stermer, Andrade, Bell, & Curtis, 2014;Cusumano & Thompson, 1997;Dakanalis et al, 2016;Jones et al, 2004;Zimmer-Gembeck, Webb, Farrell, & Waters, 2018), in the present study, girls reported higher levels of social appearance anxiety compared to boys. Finally, the present study did not find any statistically significant difference between girls' and boys' problematic social media use scores.…”
Section: Discussionsupporting
confidence: 73%
“…These debates tend to focus more on attainability, rather than the PBN. Attainability beliefs may have both disempowering consequences (e.g., increased appearance anxiety and perceived need for cosmetic surgery; Burkley et al, 2014; see also Franzoi, 2001) and empowering consequences (e.g., increasing efficacy of attractiveness-enhancing efforts; Hill et al, 2012; Netchaeva & Rees, 2016). By contrast, we argue that social demands for intense devotion to achieving beauty (i.e., the PBN) consistently disempower women via internal and external policing.…”
Section: The Pbn’s Relationship To Evolutionary and Feminist Theoriesmentioning
confidence: 99%
“…Social appearance anxiety is an important construct to investigate given its unique association with disordered eating (Levinson et al, 2013). Furthermore, social appearance anxiety has also been shown to lead to state body dissatisfaction (Levinson & Rodebaugh, 2015) and mediates the effect of exposure to "beauty-is-malleable" messages on interest in plastic surgery (Burkley et al, 2014). By considering social appearance anxiety as a measure of body image, this study corroborates Gleeson and Frith's (2006) argument that the perception of one's body is inherently social and that body image research should consider the complexity of the ways in which people perceive and evaluate their bodies in different (imagined) contexts, such as a context in which one is judged based on their appearance.…”
Section: Magazine Exposure and Social Appearance Anxietymentioning
confidence: 99%
“…Moreover, magazines targeted at young women regularly show that the ideal appearances of celebrities can be emulated through clothing, makeup, and beauty products (Duke, 2002). Therefore, early adolescents not only encounter a mere visual image of media figures who comply with the prevailing beauty standards, but are also confronted with media messages aimed to convince them that anyone can and should become attractive (Burkley et al, 2014). Although ample literature exists on the influence of appearance-focused magazines on people's body image (e.g., Slater & Tiggemann, 2014) and body dissatisfaction (e.g., Clark & Tiggemann, 2006;Tiggemann, Slater, Bury, Hawkins, & Firth, 2013), few studies have investigated the association between magazine exposure and social appearance anxiety.…”
mentioning
confidence: 99%